Penetrating critiques : emasculated empire and Victorian identity in Africa - Allin, Leslie, 1984- (University of Toronto Press, 2020)
"Tracing the intersections between archival documents and immensely popular adventure fiction set in Africa, Penetrating Critiques highlights the anxieties surrounding the vulnerability of the white male body by assessing the destabilization of narrative itself. The author considers texts ranging from private letters, governmental correspondence, periodicals, and archives to the popular works of H. Rider Haggard, Richard Marsh, and Joseph Conrad. These texts trouble the notions of bounded male bodies, impermeable histories, and solid virtues while underscoring the grotesqueness of male forms, narratives, and moralities. Although dominant representations of martial bodies frequently emphasized boundaries, containment, and solidity, the fiction and imperial archives explored in this book expose problems of stability through tropes, images, and material evidence of perforation, penetration, and dissolution. In emphasizing the relationship between institutional imperial writing and popular discourse, Penetrating Critiques reveals that more complex, fraught, and critical approaches to imperialism and masculinity were circulating throughout Victorian culture than previously recognized. "--